2019
DOI: 10.1002/cpt.1381
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Effects of Cannabis and Cannabinoids on Health

Abstract: Cannabis is the most popular illicit drug in the Western world. Repeated cannabis use has been associated with short‐ and long‐term side effects, including respiratory and cardiovascular disorders, cognitive alterations, psychosis, schizophrenia, and mood disorders. However, casual relations between cannabis use and these adverse effects are missing. On the other hand, recent research proposed promising therapeutic potential of cannabinoid‐based drugs for a wide range of medical conditions, including neurologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
149
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(164 citation statements)
references
References 100 publications
(435 reference statements)
2
149
0
13
Order By: Relevance
“…Moreover, plays a fundamental role in pregnancy outcome and fetal development, and overstimulation of CBr1 in the placenta can impair fetal growth by inhibiting cytotrophoblastic proliferation [5,28,31]. The endocannabinoid receptors can be found on both presynaptic neurons and postsynaptic locations and are densely expressed in various regions within the brain [4], and its key function in mature neurons is modulate the release of neurotransmitters [18]. These receptors has been detected in the fetal human brain as early as 14 weeks of gestation and changes across development indicating important roles in fetal central nervous system (CNS) development events [5,32] such as neuronal proliferation, migration and synaptogenesis [18,33].…”
Section: Cannabis Cannabinoids and Endocannabinoid Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, plays a fundamental role in pregnancy outcome and fetal development, and overstimulation of CBr1 in the placenta can impair fetal growth by inhibiting cytotrophoblastic proliferation [5,28,31]. The endocannabinoid receptors can be found on both presynaptic neurons and postsynaptic locations and are densely expressed in various regions within the brain [4], and its key function in mature neurons is modulate the release of neurotransmitters [18]. These receptors has been detected in the fetal human brain as early as 14 weeks of gestation and changes across development indicating important roles in fetal central nervous system (CNS) development events [5,32] such as neuronal proliferation, migration and synaptogenesis [18,33].…”
Section: Cannabis Cannabinoids and Endocannabinoid Systemmentioning
confidence: 99%
“…Over time, and adopting social rules, these substances were designated as licit or illicit according to their pharmacological properties and effects on the organism [1]. Among the various illicit substances cannabis products has been used cannabis for centuries for spiritual, medicinal and nonmedical purposes, and over the past 60 years recreational or non-medicinal use has spread globally by adolescents and youg adults, currently being the most commonly used by pregnant women that believe cannabis is natural and safer than other substances [2][3][4][5][6]. Studies have observed increased prevalence of pregnant women using cannabis in different forms.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the application of cannabis and cannabinoid drugs for the treatment of pain 17 and other neuropsychiatric disorders, in particular epilepsy, 18 has launched highly controversial discussions as there are strong differences in the national legislation of prescription and use. In this issue, Cohen et al 19 give a comprehensive review on the acute and long-term effects of cannabinoid drug use as well as their therapeutic potential and risk. The authors acknowledge that there are some positive effects of cannabinoids; however, they demand further large-scale, double-blind, placebo-controlled and comparator-controlled clinical trials to further substantiate the potential therapeutic role.…”
Section: In This Issuementioning
confidence: 99%
“…Cannabis is a genus of plants of the Cannabaceae family and contains more than 500 compounds—120 cannabinoids and 80 biologically active chemical compounds . It is known to interact with the endocannabinoid system, composed of a network of receptors (CB 1 and CB 2 ), signaling molecules, and enzymes.…”
mentioning
confidence: 99%
“…Cannabis is a genus of plants of the Cannabaceae family and contains more than 500 compounds-120 cannabinoids and 80 biologically active chemical compounds. 4,5 It is known to interact with the endocannabinoid system, composed of a network of receptors (CB 1 and CB 2 ), signaling molecules, and enzymes. Two common compounds found in cannabis are -9-tetrahydrocannabinol (THC) and cannabidiol (CBD), which are available as oral solid and semisolid dosage forms, vaporization, oils, topicals, and transdermal patches.…”
mentioning
confidence: 99%